Femtosecond Pulse Shaping With Spatial–Light Modulator Based On Twist Nematic With Homeotropic Boundary Conditions - A. P. Grigoryan; M. R. Hakobyan; R. S. Hakobyan
The possibility of femtosecond optical pulses shaping using a spatial–light modulator (SLM) based on the twisted nematic (TN) liquid crystal with homeotropic boundary conditions is theoretically considered. Phase sensitive pulse shaping using a TNSLM and the shaped waveforms are calculated. Using this kind of LC structure allows to control shaping process by electrical fields with voltages much less than 1V.
Keywords: Physics; Physics of elementary particles; Optics